Identifying political polarization in social media: a literature review - Rum, Siti Nurulain Mohd; Mohamed, Raihani; Asfarian, Auzi (Semarak Ilmu Publishing, 2024)
Online social media platforms are often responsible for the rise of fake news, which can occasionally prevent people from knowing the truth and fuels partisan political conflict. The idea of "echo chambers" and “filter-bubbles” draws attention to how social media is incredibly fragmented, individualized, and niche-focused, all of which serve to further polarize public opinion. These terms have been associated with the referendum of Brexit in the UK and the victory of Donald Trump in 2016's US presidential election. The term “homophily” on the other hand refers to the tendency of people to be in a circle that shares the same thought and interest, that could also contribute to political division in social media. In the positive side, high political polarization demonstrates the freedom of expression, on the other hand it can heighten political tensions and inequalities, which may have an adverse effect on a nation's stability. Determining political division and its origins via social media is therefore a crucial topic for discussion. In this research work, several articles were examined to discover the computing methods and approaches employed by the existing works for identifying political polarization in social media.